NEGOTIATED ORDER IN TAX AUDIT OF CORPORATE TAX - Sriningsih, Endang (Advances in Social Sciences Research Journal, 2016)
Abstract This study investigated the negotiations in taxation from the theoretical perspective of Anselm Strauss’ Negotiated Order, especially in the tax audit between Tax Auditors and Authorized Agents of Taxpayers in Surabaya, Gresik and Sidoarjo. Taxation in Indonesia applies a self-assessment system, so that taxpayers should play an active role to meet their tax compliance. However, since the system was adopted in 1984, and due to the outbreak of the issues of tax resistance, the awareness of taxpayers to meet their tax compliance has still been very low. Regarding this, the government adopts law enforcement by means of three main pillars: tax examination, investigation and collection. The study resulted in the following findings. First, implementation of joint responsibility and counter data of transaction counterparties in the tax reporting could prevent negotiations between the Taxpayer and Tax Auditor. Second, Tax Auditor applies deterrent effect in the tax audit, which resulted in degrading the taxpayer’ position, and benefitting the Tax Auditor personally. This means that there has been a "win-lose" negotiation. Third, inter-institution negotiations took place, aimed at easing the tax burden of entrepreneurs. In general, the results of this study strengthen as well as expand the negotiated order theory of Anselm Strauss, in that the structural context using a crisscrossing surveillance as an obligation between the parties that have the potential to negotiate can prevent negotiation. The negotiated order modes used in this study, namely avoidance, arrogance, influence of power, and compromise, can be added to a series of properties of Strauss’ negotiation context. Key words: negotiated order, taxation, joint responsibility, deterrent effect, self assessment.